2021
DOI: 10.1186/s12877-021-02479-1
|View full text |Cite
|
Sign up to set email alerts
|

Associations of changes in late-life blood pressure with cognitive impairment among older population in China

Abstract: Background The cognitive impact of changes in late-life blood pressure is less clear. We aimed to investigate the association between late-life blood pressure changing pattern and risk of cognitive impairment. Methods Using data from the community-based Chinese Longitudinal Healthy Longevity Survey, change in systolic (SBP) or diastolic (DBP) blood pressure was calculated as the difference between follow-up and baseline, cognitive impairment was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Among 8493 older adults (mean age, 80.6 years) in the Chinese Longitudinal Healthy Longevity Survey, those whose SBP increased from 130 to 150 mm Hg at baseline to >150 mm Hg at follow-up had 48% higher odds (95% CI, 13%−93%) of incident cognitive impairment and those whose SBP decreased from 130 to 150 mm Hg at baseline to <130 mm Hg at follow-up had 28% higher odds (95% CI, 2%−61%) of incident cognitive impairment compared with those who maintained stable SBP from 130 to 150 mm Hg. 45…”
Section: Brain Healthmentioning
confidence: 99%
“…Among 8493 older adults (mean age, 80.6 years) in the Chinese Longitudinal Healthy Longevity Survey, those whose SBP increased from 130 to 150 mm Hg at baseline to >150 mm Hg at follow-up had 48% higher odds (95% CI, 13%−93%) of incident cognitive impairment and those whose SBP decreased from 130 to 150 mm Hg at baseline to <130 mm Hg at follow-up had 28% higher odds (95% CI, 2%−61%) of incident cognitive impairment compared with those who maintained stable SBP from 130 to 150 mm Hg. 45…”
Section: Brain Healthmentioning
confidence: 99%
“…In a 9-year longitudinal study, Glynn et al (1999) found a U-shaped association between cognitive impairment and DBP and demonstrated that lower DBP (<70 mm Hg) and higher DBP (≥80 mm Hg) were associated with an increased risk of cognitive impairment. Gao et al (2021) also found that persistently low stable rather than significantly reduced DBP might be protective against cognitive impairment. Furthermore, our results suggested that lowered PP was associated with an increased risk of cognitive impairment.…”
Section: Discussionmentioning
confidence: 86%
“…Unfortunately, there are no similar studies to contrast our findings regarding specific MetS combinations. Previous studies have shown that age [ 27 ], hypertension [ 56 ], obesity [ 57 ], and hyperglycemia [ 58 ], individually, are related to cognitive function [ 59 , 60 ]. However, given the differences in experimental designs, the overall results are sometimes conflicting.…”
Section: Discussionmentioning
confidence: 99%